Modification of the B meson mass in a magnetic field from QCD sum rules - Machado, C. S. [UNESP]; Matheus, R. D. [UNESP]; Finazzo, S. I.; Noronha, J. (Amer Physical Soc, 2014)
In this paper, we extend the well-known QCD sum rules used in the calculation of the mass of heavy mesons to estimate the modification of the charged B-meson mass, m(B), in the presence of an external Abelian magnetic field, eB. Two simplifying limits were considered: the weak field limit, in which the external field satisfies eB << m(2) (with m being any of the masses involved); and the strong field limit, in which the field strength is small in comparison to the bottom quark mass (or the B-meson mass) squared, but it is large compared to the mass of the light quarks, i.e., m(u,d)(2) << eB << m(b,B)(2). We found that m(B) decreases with the magnetic field in both of these limits.